The influence of SBP amplification on the accuracy of form-factor-derived mean arterial pressure. Issue 6 (June 2020) - Schultz, Martin G.; Picone, Dean S.; Armstrong, Mathew K.; Black, J. Andrew; Dwyer, Nathan; Roberts-Thomson, Philip; Sturgess, David; Sharman, James E.
Abstract : Objectives: Accurate assessment of mean arterial pressure (MAP) is crucial in research and clinical settings. Measurement of MAP requires not only pressure waveform integration but can also be estimated via form-factor equations incorporating peripheral SBP. SBP may increase variably from central-to-peripheral arteries (SBP amplification), and could influence accuracy of form-factor-derived MAP, which we aimed to determine. Methods: One hundred and eighty-eight patients (69% men, age 60 ± 10 years) undergoing coronary angiography had intra-arterial pressure measured in the ascending aorta, brachial and radial arteries. Reference MAP was measured by waveform integration, and form-factor-derived MAP using 33 and 40% form-factors. Results: Reference MAP decreased from the aorta to the brachial (−0.7 ± 4.2 mmHg) and radial artery (−1.7 ± 4.8 mmHg), whereas form-factor-derived MAP increased (33% form-factor 1.1 ± 4.2 and 1.7 ± 4.7 mmHg; 40% form-factor 0.9 ± 4.8 and 1.4 ± 5.4 mmHg, respectively). Form-factor-derived MAP was significantly different to reference aortic MAP (33% form-factor −2.5 ± 4.6 and −1.6 ± 5.8, P  < 0.001; 40% form-factor 2.5 ± 5.0 and 3.9 ± 6.4 mmHg, P  < 0.001, brachial and radial arteries, respectively), with significant variation in the brachial form-factor required (FFreq ) to generate MAP equivalent to reference aortic MAP (FFreq range 20–57% brachial; 17–74% radial). Aortic-to-brachial SBP amplification was strongly related to brachial FFreq ( r  = −0.695, P  < 0.001). The 33% form-factor was most accurate with high aortic-to-brachial SBP amplification (33% form-factor MAP vs. reference aortic MAP difference 0.06 ± 3.93 mmHg, P  = 0.89) but overestimated reference aortic MAP with low aortic-to-brachial SBP amplification (+5.8 ± 4.6 mmHg, P  < 0.001). The opposite was observed for the 40% form-factor. Conclusion: Due to variable SBP amplification, estimating MAP via form-factors produces nonphysiological inaccurate values. These findings have important implications for accurate assessment of MAP in research and clinical settings.